Association between ultra-processed food consumption and sleep quality among students in Universiti Tunku Abdul Rahman (UTAR) - Tan, Ya Le (2025)
This cross-sectional study investigated the association between ultra-processed food (UPF) consumption and sleep quality among 324 undergraduate students at Universiti Tunku Abdul Rahman (UTAR) using the NOVA food classification system. NOVA categorizes foods into four groups based on processing level: unprocessed or minimally processed foods (UMPF), processed culinary ingredients (PCI), processed foods (PF), and ultra-processed foods (UPF). UPF are industrial formulations containing multiple artificial additives and minimal whole foods, typically high in refined sugars, unhealthy fats, and sodium including items like instant noodles, packaged snacks, and sugar-sweetened beverages. Using the NOVA classification system and the Pittsburgh Sleep Quality Index (PSQI), we assessed dietary patterns and sleep quality. Results revealed that UPF contributed a median of 521.84 kcal (27.87%) in daily caloric intake, which is the second largest contributor. A significant majority (n=221, 68.2%) of students exhibited poor sleep quality (PSQI > 5). Spearman’s correlation analysis demonstrated a moderate positive association between UPF consumption and poorer sleep quality (ρ = 0.48, p < 0.001), with female students reporting significantly worse sleep than males (p = 0.044, <0.05). Key mechanisms linking UPF to sleep disturbances included gut-brain axis dysregulation, systemic inflammation, and neurotoxic additives. Despite limitations such as self-reporting bias and a predominantly Chinese sample, this study highlights UPF as a modifiable risk factor for sleep disorders in Malaysian university students. Interventions targeting dietary habits and sleep hygiene are recommended to improve student well-being.